2015
DOI: 10.1051/epjconf/20159303009
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the12C+12C fusion cross section for astrophysics

Abstract: Abstract. The 12 C+ 12 C reaction is one of the single most important nuclear reactions in astrophysics. It strongly influences late evolution of massive stars as well as the dynamics of type Ia supernovae and x-ray superbursts. An accurate estimation of the cross section at relevant astrophysical energies is extremely important for modeling these systems. However, the situation is complicated by the unpredictable resonance structure observed at higher energies. Two recent studies at Notre Dame have produced r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Due to their importance for a variety of stellar environments, in particular in Type 1a SN studies, these reaction rates are currently under much investigation (e.g. Bucher et al 2015). Chen et al (2014) examined the impact of variations to the 12 C + 12 C rates on carbon burning within super-AGB stars and found that if the rates were multiplied by factors of 1 000 and 0.01, the minimum CO core mass for carbon ignition became 0.93 M and 1.10 M , respectively.…”
Section: Doherty Et Almentioning
confidence: 99%
“…Due to their importance for a variety of stellar environments, in particular in Type 1a SN studies, these reaction rates are currently under much investigation (e.g. Bucher et al 2015). Chen et al (2014) examined the impact of variations to the 12 C + 12 C rates on carbon burning within super-AGB stars and found that if the rates were multiplied by factors of 1 000 and 0.01, the minimum CO core mass for carbon ignition became 0.93 M and 1.10 M , respectively.…”
Section: Doherty Et Almentioning
confidence: 99%
“…This resonance has been posited to explain the discrepancy between the observed and predicted superburst ignition depth, much in the way the Hoyle state was predicted to explain cosmic carbon production [207]. However, present experimental constraints are contradictory and rely on theoretical extrapolations [208].…”
Section: Nuclear Sensitivities and Recent Uncertainty Reduction Effortsmentioning
confidence: 99%